MCMSim Test-Bed for Multi-Channel MAC Framework For MANET - Kumar, Rohit; Taneja, Kavita; Taneja, Harmunish (International Journal of Computer Sciences and Engineering, 2019)
With the rising computational capacity requirements and ubiquitous computing, newer and powerful hardware and software platforms are being created. These newer powerful architectures and platforms are significantly different from their conventional predecessor architectures. These new platforms need to be evaluated, tested and validated for performance measurement before the product release. In the area of mobile ad hoc networks the use of multiple communication channels has emerged as a powerful new hardware platform which can increase the capacity manifold. But one major problem faced by researchers is that the traditional simulation tools don’t support these improved hardware platforms. So to carry out performance analysis of these platforms new test-beds and simulators are required to be developed. In the proposed work a software simulation test-bed for multi-channel Medium Access Control framework for mobile ad hoc Networks (MANET) has been developed and is named MCMSim.